Tagging the initial-state gluon - Simone Caletti; Oleh Fedkevych; Simone Marzani; Daniel Reichelt (European Physical Journal C: Particles and Fields, 2021)
Abstract We study the production of an electroweak boson in association with jets, in processes where the jet with the highest transverse momentum is identified as quark-initiated. The quark/gluon tagging procedure is realised by a cut on a jet angularity and it is therefore theoretically well-defined and exhibits infrared and collinear safety. In this context, exploiting resummed perturbation theory, we are able to provide theoretical predictions for transverse momentum distributions at a well-defined and, in principle, systematically improvable accuracy. In particular, tagging the leading jet as quark-initiated allows us to enhance the initial-state gluon contribution. Thus these novel transverse momentum distributions are potentially interesting observables to probe the gluonic degrees of freedom of the colliding protons.